LONG TERM EVOLUTION OF BONE RECONSTRUCTION WITH BONE GRAFT SUBSTITUTES - Martynenko, O. V.; Zolochevsky, O. O.; Allena, R. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2017)
The review involves clinical and experimental data, constitutive modeling, and computational investigations towards an understanding on how mechanical cyclic loads for long periods of time affect damage evolution in a reconstructed bone, as well as, lifetime reduction of bone graft substitutes after advanced core decompression. The outcome of the integrated model discussed in this paper will be how damage growth in femur after advanced core decompression subjected to mechanical cyclic loading under creep and fatigue conditions may be controlled in order to optimize design and processing of bone graft substitutes, and extend lifetime of bone substitutes.